V. Solovyov’s Philosophical Model of an Ideal Society (On the Formation of the “All-Unity” Conception) - Šliogeris, Arvydas (Problemos, 1972)
V. Solovyov’s philosophy appeared in the post-reform Russia when the social structure of the country was subject to important changes caused by the impact of a rapid growth of capitalism. The elements of the old serfdom and feudal structure, on the other hand, were still offering resistance to the development of capitalist forms of society. The Russian intellectuals of that time were seriously anxious about the future history of their homeland. That problem was being solved by presenting a variety of models to remake the existing social structure of Russia. V. Solovyov undertook the task of overcoming the social contradictions of his society through a “renovated” Christian consciousness. It was this “renovation” suggested by V. Solovyov that served as a basis for his philosophy of “All-unity” which, in its turn, is considered to be a mystical-philosophical model of an ideal society free of class struggle and other social contradictions, i.e., an antipode of capitalism. The author of the present article shows the "All-unity" conception to be deeply reactionary at that historical situation.